Folded ring slot antenna reader for UHF RFID applications using artificial magnetic conductor structure. Issue 12 (22nd September 2016) - Marques, D.; Egels, M.; Pannier, P.
ABSTRACT: This article presents a new design of an UHF RFID reader antenna with a circular polarization and radiation pattern in one hemisphere. This antenna consists of two parts which are a radiating element and an artificial magnetic conductor (AMC) structure. The radiating element is based on a slot ring antenna using a folding technique for rings and only one feeding source while keeping a circular polarization. The AMC structure is a simple patch structure using a size reduction technique. The possibility to mix with two different materials for substrates involves the realization of six antennas which are presented in this article. Their overall is 226 mm × 226 mm × 11.06 mm. The antenna with the best performances in the UHF‐RFID‐ETSI band has a gain of 6.9 dBic and an axial ratio of 3dB. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2790–2794, 2016